Accelerated Carbonation of Steel Slags Using CO2 Diluted Sources: CO2 Uptakes and Energy Requirements - Baciocchi, Renato; Costa, Giulia; Polettini, Alessandra; Pomi, Raffaella; Stramazzo, Alessio; Zingaretti, Daniela (Frontiers in Energy Research, 2016)
This work presents the results of carbonation experiments performed on Basic Oxygen Furnace (BOF) steel slag samples employing gas mixtures containing 40 and 10% CO2 vol. simulating the gaseous effluents of gasification and combustion processes respectively, as well as 100% CO2 for comparison purposes. Two routes were tested, the slurry phase (L/S=5 l/kg, T=100 °C and Ptot=10 bar) and the thin film (L/S =0.3-0.4 l/kg, T=50 °C and Ptot=7-10 bar) routes. For each one, the CO2 uptake achieved as a function of the reaction time was analyzed and on this basis the energy requirements associated to each carbonation route and gas mixture composition were estimated considering to store the CO2 emissions of a medium size natural gas fired power plant (20 MW). For the slurry phase route, maximum CO2 uptakes ranged from around 8% at 10% CO2, to 21.1% (BOF-a) and 29.2% (BOF-b) at 40% CO2 and 32.5% (BOF-a) and 40.3% (BOF-b) at 100% CO2. For the thin film route, maximum uptakes of 13% (BOF-c) and 19.5% (BOF-d) at 40% CO2, and 17.8% (BOF-c) and 20.2% (BOF-d) at 100% were attained. The energy requirements of the two analyzed process routes appeared to depend chiefly on the CO2 uptake of the slag. For both process route, the minimum overall energy requirements were found for the tests with 40% CO2 flows (i.e. 1400-1600 MJ/t CO2 for the slurry phase and 2220-2550 MJ/t CO2 for the thin film route).